TEMPERAMENT AND CHARACTER AS A SINGLE BASIS OF HUMAN ACTIVITIES - Abitkhan Sabitkhanovich Shakirov (Western European Studies, 2024)
analysis of character and types of temperaments is the basis for any activity of the human factor, whether in a team, in a family or in natural nature. Types of temperaments are parameters that allow assessing the capabilities of a person as a reasonable person. The article is devoted to the disclosure of the concept of "temperament", its influence on character and on the way of life and way of thinking of a person.
Keywords: typology; management; motivation